Inhibition of dengue virus infection by trifluoperazine - Piccini, Luana Érica (2022)
Dengue virus (DENV), a member of the genus Flavivirus, family Flaviviridae, is the most widespread viral pathogen transmitted to humans by mosquitoes. Despite the increased incidence of DENV infection, there are no antiviral drugs available for treatment or prevention. Phenothiazines are heterocyclic compounds with various pharmacological properties that are very adaptable for drug repurposing. In the present report, we analyzed the antiviral activity against DENV and the related Zika virus (ZIKV) of trifluoperazine (TFP), a phenothiazine derivative in clinical use as an antipsychotic and antiemeticagent. TFP exhibited dose-dependent inhibitory activity against the four DENV serotypes and ZIKV in monkey Vero cells at non-cytotoxic concentrations with 50% effective concentration values in the range 1.6-6.4 μM. A similar level of antiviral efficacy was exhibited by TFP against flavivirus infection in the human cell lines A549 and HepG2. Mechanistic studies, performed using time-dependent infectivity assays, real-time RT-PCR, Western blot, and immunofluorescence techniques, indicated that uncoating of the virus during penetration into the cell was the main target for TFP in infected cells, but thecompound also exerted a minor effect on a late stage of the virus multiplication cycle. This study demonstrates that TFP, a pharmacologically active phenothiazine, is a selective inhibitor of DENV multiplication in cell culture. Our findings open perspectives for the repositioning of phenothiazines like TFP with a wide spectrum of antiviral efficacy as potential agents for the control of pathogenic flaviviruses.